Analysis of Financial Behavior on the Investment Decisions of Civil Servants in the Class I Checkpoint Immigration Office Malang - Zulfikar Fatoni; Marissa Ulfa Musdalifa; Elis M. Liandana (Transpublika Publisher, 2025)
Every investment requires good decisions, as these decisions will affect future investment returns. Public access to financial products and services continues to increase and is increasingly accessible, but without good financial understanding and management, this will not have a positive impact, especially for the younger generation. The purpose of this study was to determine financial behavior towards Civil Servants (ASN) investment decisions within the Class I Checkpoint Immigration Office Malang. The research method used is qualitative, which describes each variable used. The results of this study concluded that the results of financial behavior literacy affect the way an individual thinks about financial conditions and affect ASN investment decision making within the Class I Checkpoint Immigration Office Malang. In addition, it also shed light on the strategies in terms of finance and better management will make it easier for Civil Servants (ASN) to live their daily lives.